Neural representations for newly learned words are modulated by overnight consolidation, reading skill, and age. (March 2018) - Landi, Nicole; Malins, Jeffrey G.; Frost, Stephen J.; Magnuson, James S.; Molfese, Peter; Ryherd, Kayleigh; Rueckl, Jay G.; Mencl, William E.; Pugh, Kenneth R.
Abstract: Word learning depends not only on efficient online binding of phonological, orthographic and lexical information, but also on consolidation of new word representations into permanent lexical memory. Work on word learning under a variety of contexts indicates that reading and language skill impact facility of word learning in both print and speech. In addition, recent research finds that individuals with language impairments show deficits in both initial word form learning and in maintaining newly learned representations over time, implicating mechanisms associated with maintenance that may be driven by deficits in overnight consolidation. Although several recent studies have explored the neural bases of overnight consolidation of newly learned words, no extant work has examined individual differences in overnight consolidation at the neural level. The current study addresses this gap in the literature by investigating how individual differences in reading and language skills modulate patterns of neural activation associated with newly learned words following a period of overnight consolidation. Specifically, a community sample of adolescents and young adults with significant variability in reading and oral language (vocabulary) ability were trained on two spoken artificial lexicons, one in the evening on the day before fMRI scanning and one in the morning just prior to scanning. Comparisons of activation between words that were trained and consolidated vs. those that were trained but not consolidated revealed increased cortical activation in a number of language associated and memory associated regions. In addition, individual differences in age, reading skill and vocabulary modulated learning rate in our artificial lexicon learning task and the size of the cortical consolidation effect in the precuneus/posterior cingulate, such that older readers and more skilled readers had larger cortical consolidation effects in this learning-critical region. These findings suggest that age (even into late adolescence) and reading and language skills are important individual differences that affect overnight consolidation of newly learned words. These findings have significant implications for understanding reading and language disorders and should inform pedagogical models. Highlights: No extant work has examined individual differences in word learning following overnight consolidation at the neural level. We investigate whether skill modulates neural activation to newly learned words following overnight consolidation. Older readers and more skilled readers show larger cortical consolidation effects.